The Quality of the Content of Preschool Education in Ukraine at the End of the Twentieth Century: Impact of Social and Economic Factors - Frolenkova, Nadiya (Pedagogical Discourse, 2014)
Аt the end of the twentieth century Ukraine’s transition to democracy, the rule of law and market economy needed a radical reform of the education system. On the basis of summarizing it was found out that in the last decade of the last century the system of preschool education has undergone major changes, feeling both positive and negative effects. Following that the changes were caused not so much targeted policy reform education as long the crisis in the economic and social development in general. Socio-economic and socio-political factors that influenced the content of Ukrainian pre-school education, its quality, in the late twentieth century have been revealed. Classification of factors of influence has been characterized, their features have been examined. The attention is concenrated on the fact that despite the socio-economic difficulties of the first decade of education in independent Ukraine creatively worked and continue to work, and scholars and practitioners, providing quality preschool education. This problem is considered in socio-economic terms.